Case Report: Detection of Double ROS1 Translocations, SDC4-ROS1 and ROS1-GK, in a Lung Adenocarcinoma Patient and Response to Crizotinib - Xu, Long; Chen, Xiaoxia; Huo, Hong; Liu, Yongye; Yang, Xiaodan; Gu, Dejian; Yuan, Mingming; Zhang, Min; Chen, Rongrong; Wang, Jiayin; Zheng, Zhendong (Frontiers in Medicine, 2021)
ROS1 rearrangement, identified in ~2% of non-small cell lung cancer (NSCLC), has defined a distinctive molecular subtype. Patients with ROS1 fusion have been shown to be highly sensitive to treatment with crizotinib. However, the efficacy of crizotinib in NSCLC patients with double ROS1 fusions remains to be elucidated. Here, we report a 40-year-old male diagnosed with stage IIIA lung adenocarcinoma. Two ROS1 fusions [SDC4-ROS1 (EX2:EX32) and ROS1-GK (EX31:EX13)] were detected simultaneously in tumor tissue of this patient by next-generation sequencing. Crizotinib was administered, and the patient showed a partial response in lung lesions. Nevertheless, a brain lesion was found at 8 months after treatment. The slightly short duration of response may be related to the presence of ROS1-GK rearrangement. This case proved that patients with SDC4-ROS1 and ROS1-GK fusions may be sensitive to crizotinib, but short progression-free survival of this case showed that the presence of ROS1-GK rearrangement may affect the efficacy of crizotinib. A large-scale investigation on the efficacy of ROS1 inhibitors in patients with complex ROS1 fusions should be conducted in the future.